SECONDARY PROFESSIONAL EDUCATION: ORGANIZATION OF EDUCATIONAL PROCESS - Alexander A. Listvin (Russian State Vocational Pedagogical University, 2015)
Purpose: The paper considers possible ways of organizing a regional system of continuing education based on the experience analysis of vocational institutions in the Vologda region.Results: Implementation of the lifelong learning paradigm calls for changing the status, structure and content of secondary vocational education, given the innovative growth of domestic economy. However, the previous positive experience in vocational training should be preserved and transformed according to the current demands.Scientific novelty: The research findings include the main formation concepts of continuing education system implying the integration of professions and their groups in particular industries, diversification and differentiation of educational process.Practical significance: The recommended model of vocational training, based on the wide integration of group-generating professions, is relevant in the situation of decreasing demand for workforce reproduction and ever changing list of required professions. The given model meets the demands for secondary vocational education in terms of flexibility, dynamics, differentiation and individualization of education.